การวิเคราะห์เปรียบเทียบการเผาไหม้เและสมรรถนะของน้ำมันปาล์มดิบ น้ำมันปาล์มโอลีอินและน้ำมันดีเซล ในเครื่องยนต์จุดระเบิดด้วยการอัดขนาดเล็ก - พิพัฒน์ ตันติเวชการวงศ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
The objectives of the study are aimed to study the effects of Crude Palm Oil (CPO) and Palm Olein Oil on engine combustion phenomenon and engine performance compared with using diesel. The study also extends to investigate the effects of fuel injection timing on the engine combustion. This study had been conducted with the CI engine, KUBOTA model RT140 DI. The study was divided into three parts. First part was performance testing on a dynamometer. The combustion were analyzed using in-cylinder pressure data of these three types of fuels. While testing CPO and Palm Olein Oil, the effects of injection timing were also investigated. It was found that advanced injection timing will give the highest in-cylinder pressure but it was decreased when the retarded timing were set. With the change of fuel injection timing, heat release rate, integrated heat release and mass fraction burned were changed. Moreover, ignition delay will become shorter and burn duration will become longer when the injection timing is more retarded. The second part of the study was determining the proper injection timing of using CPO and using Palm Olein Oil by determining the optimum specific fuel consumption and the brake fuel conversion efficiency when the frequency from the standard testing method, ESC Test Cycle, had been applied. The study has shown that OEM’s injection timing was the most proper injection timing for both CPO and Palm Olein Oil. However, from the results of analyzing the combustion of these three types of fuel at standard injection timing, it was found that the engine using diesel has more retard in injection timing than the engine using CPO and Palm Olein Oil. The obtained maximum heat release rate, integrated heat release and mass fraction burned of engine fueled with the CPO and the Palm Olein Oil were lower than diesel. At low-load conditions, the maximum values of in-cylinder pressure when fueling with CPO and with Palm Olein Oil were higher than that of fueling with diesel. And at high-load conditions, the results were in the opposite way. The third part was performance test at steady state, constant speed conditions on dynamometer by using the proper injection timing (OEM’s injection timing). The study has shown that the maximum torque of the engine using Palm Olein Oil was closed to the maximum torque of the engine using diesel but the maximum torque of the engine using CPO was approximately 3.6% lower than the others. Specific fuel consumption of the engine using CPO was not different from using Palm Olein Oil but both were higher than using diesel. The highest fuel conversion efficiency of using CPO and using Palm Olein Oil were lower than that using diesel. Exhaust temperatures of the engine using CPO and using Palm Olein Oil were higher than the engine fueled with diesel. Smoke density of the engine using CPO was higher than the engine using diesel and was a little higher than the engine using Palm Olein Oil. Finally, this study can be concluded that diesel could be replaced by CPO and Palm Olein Oil. The study shown that if this engine’s model, which using in this study, was brought to regular use, the standard fuel OEM’s injection timing can be the best match for these two types of Palm Oils.